2015
DOI: 10.1155/2015/254260
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Complications in Cutaneous Lupus Erythematosus: A Systematic Review with a Meta-Analysis of Reported Cases

Abstract: Ocular complications associated with cutaneous lupus erythematosus (CLE) are less studied compared with those ones associated with systemic lupus erythematosus (SLE). The main ocular sites involved in patients affected by discoid lupus erythematosus (DLE) are eyelids followed by orbit and periorbit, the least being cornea. The most common complications are blepharitis usually affecting the lower lid and associated with some type of lid lesion such as plaque or erythematosus patches and madarosis. Few cases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 62 publications
2
18
0
Order By: Relevance
“…Ocular complications of DLE typically manifests as lesions on the eyelids or with conjunctivitis, both of which this patient did not have, suggesting he had both DLE with active lesions in addition to THS. 9 This unusual occurrence of THS and DLE prompts consideration of nonsystemic autoimmune disorders in diagnosis of THS.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular complications of DLE typically manifests as lesions on the eyelids or with conjunctivitis, both of which this patient did not have, suggesting he had both DLE with active lesions in addition to THS. 9 This unusual occurrence of THS and DLE prompts consideration of nonsystemic autoimmune disorders in diagnosis of THS.…”
Section: Discussionmentioning
confidence: 99%
“…Periorbital edema is a rare presentation of CLE . A review of 77 patients with CLE and ocular findings by Arrico et al revealed that the main ocular site involved is the eyelids in 63 patients (88.7%) followed by orbit and periorbital tissues in six (8.4%) and cornea in two (2.6%). These findings were most common in discoid lupus erythematosus (DLE) (92.2%) followed by lupus erythematosus profundus (7.8%) …”
Section: Discussionmentioning
confidence: 99%
“…Discoid lupus erythematosus (DLE) is the most common form of CCLE, generally involving the face (forehead, philtrum, malar region, nose, ears, and cheek) in a longstanding and disfiguring way [3].…”
Section: Introductionmentioning
confidence: 99%
“…Blepharitis and infiltrated erythematous plaques, with skin atrophy, scarring, and telangiectasia are most frequently observed [3,4]. The lower eyelid is also commonly affected, usually with loss of eyelashes (madarosis) [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation